Blended chitosan and poly(vinyl alcohol) membranes for the pervaporation of methanol and methyl tert-butyl ether - Mohd. Sakri, Norhaslina (2009)
In this research project, blended chitosan/poly(vinyl alcohol) (PVA) membranes were produced by mixing PVA and chitosan solutions. Chitosan (CS) was first dissolved in acetic acid aqueous solution before PVA solution was added. The mixture was then cured at room temperature. The modified composite membrane was prepared by coating the mixture of chitosan and PVA solution onto the porous polysulfone membrane by the solution casting technique. The porous polysulfone substrate was prepared via phase inversion process from a casting solution containing 12 wt% polysulfone, 11 wt% polyethylene glycol and 77 wt% N,N- dimethylacetamide. The weight percent of chitosan in the membrane was varied from 20 wt. % to 100 wt. % while the membrane thickness was in the range of 15-30 µm. The unmodified and modified composite membranes with PVA were used in pervaporation separation of methanol/methyl-tert-butyl ether (MTBE) mixture. The swelling degree and the total flux increased with increasing chitosan content in the membranes. 30 wt. % of methanol (MeOH) in feed was chose since it gave the optimal overall pervaporation characteristics in terms of flux and separation factor. The membrane containing chitosan 20 wt. % to 40 wt. % performed the best. At operating temperature of 50 oC for 20 wt % to 40 wt % of chitosan, the fluxes obtained are at 52.28 g/m2.hr and 66.92 g/m2.hr with the separation factors of 81.00 and 53.22 respectively. The effect of temperature on flux followed the Arrhenius relationship. The membrane showed excellent performance for separation of MeOH/MTBE mixture when the quantity of MeOH in feed is small. It is a very suitable process for the recovery purpose in order to remove excess MeOH in the MTBE system.